The Making of Smart Citizenry: Decoding ‘Smart Citizen’ - Deepak KUMAR (Smart Cities and Regional Development Journal)
Ayona Datta (2017) highlights how the digital turn in the post-colonial cities in India has allowed the coercive power of state to control and discipline citizenry by making them actively engage in governance; while the active citizenry is just a smokescreen, a proxy to provide the larger legitimacy to the smart city project and rather the citizenry is paternalised and handheld through the emerging technologies of government. She argues, in the process, the emergence of alternative citizenry is cast and their reflections need to be gauged from the perspective of subaltern and others who defy the digital turn and its wider network. In this backdrop, the article examines the discursive construction of ‘smart citizenry’ under India’s Smart Cities Mission. Drawing on the discourse analysis of 100 smart city proposals, the article contends that the Mission creates a false binary of active and passive citizenship with implications on the citizenship rights. It is further argued that that the Mission has a very narrow understanding of active citizenship, limited to just giving tacit consent to smart city projects. This is depicted in proposals calling for smart, active, duty-bearing, responsible citizenry lack of which risk jeopardize the success of smart cities.